PERBANDINGAN KUALITAS DNA DENGAN MENGGUNAKAN METODE BOOM ORIGINAL DAN BOOM MODIFIKASI PADA ISOLAT Mycobacterium tuberculosis 151 - Farmawati, Dewi Andayani; Wirajana, I Nengah; Chandra Yowani, Sagung (Jurnal Kimia (Journal of Chemistry), 2015)
Tuberculosis (TB) is a disease caused by the Mycobacterium tuberculosis . Isolation  DNA is a necessary step to obtain the bacterial chromosomal DNA used in the Polymerase Chain Reaction (PCR). Boom isolation method is an isolation method commonly used in isolation DNA of M. tuberculosis. In Bali, the isolation DNA of M. tuberculosis conducted at the Laboratory of Biomolecular FK UNUD uses boom modification method. This research aims to compare the quality of DNA produced by the Boom methods and Boom modification methods. This research was started with the isolation process using Boom method and Boom modification  and subsequently amplified by PCR. Detection of PCR products was performed with electrophoresis method. DNA quality was determined by the thickness of bands DNA PCR product and purity analysis by spectrophotometry UV-Vis. The results obtained show that the quality of DNA Mycobacterium tuberculosis 151  isolate using Boom modification method (Laboratory of Biomolecular FK UNUD) is relatively better than Boom original methods (Boom et al, 1990).
Keywords: Tuberculosis, Mycobacterium tuberculosis, DNA isolation, isolation method, DNA quality